A global health model integrating psychological variables involved in cancer through a longitudinal study - Macía, Patricia; Gorbeña, Susana; Barranco, Mercedes; Iglesias, Nerea; Iraurgi, Ioseba (Frontiers in Psychology, 2022)
Objective: The literature has shown the relevance of certain psychological variables in adjustment to cancer. However, there is a great variability and these features could be modified through the disease process. The aim of this study is to provide an integrated and global perspective of the importance of variables such as coping, resilience, emotional control, social support, affect, and others in cancer patients through a longitudinal study, with the objective of exploring their associations and underlying interactions. Methods: The sample was composed by 71 people diagnosed with cancer who were attending psychological support at the Spanish Association Against Cancer (Biscay). We assessed the following variables in two periods of 6 months: perceived stress (PSS), emotional control (CECS), resilience (CD-RISC), coping strategies (CERQ), personality (NEOFFI), social support (MOSS), affect (PANAS), emotional distress (GHQ), quality of life (SF-12) and visual-analogic scales (EVA). Results: Results showed predictive effects of perceived stress on physical health perception (β= -.22; t= -3.26; p=.002). Mental health perception was influenced by almost all the psychological variables. Consciousness at baseline (βCo= .15; p= .003), change in Extraversion (βEx=.16; p= .001) and Resilience (βRe= .15; p= .002) had significant effects on perceived mental health. Conclusion: This study provides a global health model that integrates and explores associations between psychological variables related to cancer disease. This information could be useful for guiding personalised psychotherapeutic interventions, with the aim of increasing adjustment to disease.